Practice-led: designing through making - Dolah, Mohd Shahrizal; Rust, Chris; Abdul Rahman, Ahmad Rizal; Ramli, Saiful Hasley; Chen, Yen Fu (Faculty of Design & Architecture, Universiti Putra Malaysia, 2018)
This paper has investigated a design method for furniture designers in Malaysia to allow users to express their needs and aspirations through place making or creation of meaningful office workspaces. During the field work, we discovered that there were problems in getting the users to explain their ideas through verbal explanations. They did not have the proper techniques and tools to express their ideas. From there we started to use mock-ups as tools to communicate and engage with the respondents in our investigation. In the research, we have identified a promising participatory design approach, role-play with mock-ups. The study revealed that, by using role-play with mock-ups directly with the users, allowed the designers to quickly become aware of arising issues without the need to do a potentially time-consuming, normative and tedious observational study. This research approach is primarily leads to new understanding about practice and described as “practice-led” approach to research. This project had investigated, demonstrated and opened the possibility that these approaches could be turned into a practical participatory process toward design and place making in furniture industry practice in Malaysia.